Anxiety and depression among women with and without infertility problem in selected centers in kathmandu, Nepal. - Shrestha,Samir (2020)
ABSTRACT: Infertility is one of the neglected public health problems around the world. Infertility is a stressful life event and anxiety and depression are common in infertile women. It was a quantitative cross-sectional study with objective of study with the aim to determine the severity of anxiety and depression with fertility status and find its association with demographic and socio-economic and health related factors. The study was carried out in two centers which were providing infertility treatment service as well as ob/gyn OPD service. The sampling method was stratified systematic simple random method.The study included 177 women of whom 91were without fertility problem and 86 with fertility problem. Interview schedule was used for the socio-demographic and health related variables. To assess the anxiety and depression validated Nepali version of HADS was used. Pearson's Chi-square test and binary logistic regression was used to establish the association between anxiety and depression with fertility status and other socio-demographic and health related variables. Both the groups were comparable with respect to age, socioeconomic status, occupation, education, religion, income perception, and ethnicity. No significant differences found between both groups with respect to the socio-demographic profile. Prevalence of anxiety in my study was 23.1 percent and 46.5 percent in fertile and infertile women, likewise prevalence of depression is 5.5 percent and 36 percent in fertile and infertile women respectively. Occupation, marriage duration, support from husband and relation difficulties were associated with anxiety and depression. This study revealed that anxiety and depression was more in infertile women. Anxiety was associated with occupation, duration of marriage, supports from husband and relation difficulties Depression was associated with occupation, duration of marriage, support from husband, relation difficulties and moderate activities or sports among women. The prevalence of the problem recommends there should not be too late to address the mental health issues.